0-Hecke modules for Young row-strict quasisymmetric Schur functions. (May 2022) - Bardwell, Joshua; Searles, Dominic
Abstract: We construct modules of the 0-Hecke algebra whose images under the quasisymmetric characteristic map are the Young row-strict quasisymmetric Schur functions. This provides a representation-theoretic interpretation of this basis of quasisymmetric functions, answering a question of Mason and Niese (2015). Additionally, we classify when these modules are indecomposable.